The Principal's Strategies in Teacher Professional Development in Public Junior High Schools in Jambi Province - Muhajirin; Maisah; Kemas Imron Rosadi (International Journal of Educational and Life Sciences, 2024)
This research explores the strategies implemented by school principals in improving teacher professionalism in public junior high schools in Jambi Province. The study focuses on identifying key factors that influence the success of professional development programs, examining the role of school leadership, and addressing the challenges faced in the implementation of these strategies. The findings indicate that the strategies employed by principals, such as structured planning, the establishment of learning communities, and motivational leadership, have had a positive impact on teacher engagement and professional growth. However, challenges such as varying teacher competencies, limited technological resources, and inconsistent participation in professional development programs persist, hindering the full potential of these strategies. School principals, particularly in schools such as SMP Negeri 6 Sungai Penuh, SMP Negeri 8 Muaro Jambi, and SMP Negeri 7 Tanjung Jabung Timur, play a critical role in fostering an environment conducive to teacher development through motivation, constructive feedback, and collaborative efforts. The study suggests that improving mentoring programs, enhancing technological infrastructure, and providing flexible training schedules can address the existing barriers. These findings contribute to the growing body of knowledge on the effectiveness of leadership strategies in improving teacher professionalism and have implications for future educational reforms in Jambi Province and beyond.